Interdental brushes, from theory to practice - Natalia Asquino; Fabiana Villarnobo (Odontoestomatología, 2019)
Interproximal brushes are an interdental hygiene tool with diverse indications that have multiple benefits. Among other uses, they are indicated in patients with periodontal disease, with papillae that do not fill the interdental space, patients with orthodontic appliances, fixed prosthesis or implant.supported prosthesis. The aim of this article is to provide guidance on their clinical use based on the available evidence. The results support their use in combination with dental floss for preventing and treating the most prevalent oral diseases, with a significant effect on biofilm control and gingival inflammation.